A Chain of porcelain, a road of pearls [videorecording] treasures from the Pandanan wreck. - Medina, Susan Calo (Travel time, 1996)
Features the discovery and underwater excavations of Pandanan wreck : 15th century porcelain and other treasures ; and pearl farm managed by Eco Farm Systems & Resources, Inc. in Palawan.